2020
DOI: 10.1037/ser0000348
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing advocacy for individuals in poverty: The role of a poverty simulation training.

Abstract: Psychologists have a responsibility to be advocates for the individuals they serve within public service settings, and there is a need to identify or develop training strategies to support these efforts. Low-income families are a subset of consumers who frequently require services within these settings yet also may face providers who are not optimally supportive. One factor that interferes with providers' ability to engage in empathic, well-informed, and effective advocacy is their underlying attributions abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 64 publications
(130 reference statements)
1
9
0
Order By: Relevance
“…The Meaux study 16 showed significant improvement in 12 items; the Garrett‐Wright study 17 showed significant improvement in 11 items, with a significant worsening of attitudes toward people living in poverty in four of the 21 items. Still other researchers have experienced great benefit when using the CAPS poverty simulations 18–21 …”
Section: Introductionmentioning
confidence: 99%
“…The Meaux study 16 showed significant improvement in 12 items; the Garrett‐Wright study 17 showed significant improvement in 11 items, with a significant worsening of attitudes toward people living in poverty in four of the 21 items. Still other researchers have experienced great benefit when using the CAPS poverty simulations 18–21 …”
Section: Introductionmentioning
confidence: 99%
“…Lastly, it is common for educational simulations in other domains to be evaluated as we have here (i.e., for impacts on the participants post-simulation) [95,96], and it would be advantageous to expand this approach to other environmental simulations. In particular, the other climate-change-related simulations that have been developed, including ones focused on a social dilemma, could be tested in this way.…”
Section: Discussionmentioning
confidence: 99%
“…Advocacy for and with individuals who experience poverty has long been a focus of social justice efforts, yet provider misconceptions stemming from inappropriate causal attributions that emphasize individuals’ personal responsibility for their poverty reduce provider empathy and impede advocacy efforts. Engler and coauthors (2020) present a novel poverty simulation training program that reduces individual-level attributions and enhances participants’ understanding of external causes of poverty. Although this pilot does not assess long-term changes resulting from program participation, it demonstrates promise for shifting attributions.…”
Section: Advocacy In Specific Settings and With Specific Populationsmentioning
confidence: 99%